Hubungan Antara Pengetahuan dan Sikap Ibu Nifas Terhadap Pemilihan Metode Kontrasepsi di Puskesmas Puter Kota Bandung - Titi Purwitasari Handayani (STIKes Karsa Husada Garut, 2018)
Family planning services during childbirth is the best because at this point the motivation for family planning was highest. Therefore, knowledge is critical behaviors or attitude especially of the choice of contraceptive methods is one important aspect of the various types of contraceptive devices or appropriate means and effective, especially for puerperal woman. To determine the correlation between Knowledge with Attitude Puerperial Woman at Contraceptive Method Choosing in Puter Health Centers Bandung City. Analytic cross – sectional and the sampel taken using consecutive sampling with primary data and secondary data obtained through questionnaires to 31 respondents in Puter Health Center Bandung City. The data presented in the form frequency distribution, cross tab and then used Chi – Square test . But because of the limitations of the Chi – Square test so using Fisher's test by combining the two categories. The results showed most respondents have sufficient knowledge of the adequate category 21 respondents (67.7%) with attitude of puerperial woman as positive category 16 Respondents (51.6%). Conclusion, there was a significant Correlation between knowledge with attitude puerperial woman at contraceptive method choosing, where the P-value = 0.037 < 0.05.